Pengaruh Adopsi E-Commerce terhadap Kinerja Penjualan Usaha Mikro, Kecil, dan Menengah (UMKM) di Indonesia - Ican Kumala; Furqan Khalidy (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2026)
This study aims to analyze the effect of e-commerce adoption on the sales performance of Micro, Small, and Medium Enterprises (MSMEs) in Indonesia. E- commerce adoption factors are measured through the dimensions of platform usage, technology integration, and digital marketing activities. Sales performance is assessed based on sales growth, market expansion, and increase in customer numbers. The research method uses a quantitative approach by distributing online questionnaires to 250 MSME owners in five major cities (Jakarta, Surabaya, Bandung, Medan, Makassar) who have used at least one e-commerce platform (such as Tokopedia, Shopee, Bukalapak, or a standalone website) for at least one year. Data were analyzed using multiple regression analysis techniques with the help of SPSS 25 software. The results show that e-commerce adoption has a significant positive effect on the sales performance of MSMEs. Specifically, technology integration (such as the use of inventory management and digital payment tools) and digital marketing activities (advertising and promotions on social media) are the most dominant factors. These findings provide practical implications for MSME owners and policymakers to further encourage digitalization by providing training and supporting infrastructure.